Peningkatan Kebersihan Lingkungan melalui Edukasi Pengelolaan Sampah dan Kerjasama Masyarakat di Kota Surabaya - Jahroni Jahroni; Riyadh Mahrus; Arif Rachman Putra; Didit Darmawan; Rafadi Khan Khayru (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Waste management issues are crucial issues that require integrated handling and cross-sector collaboration, especially in urban areas such as Surabaya. This community service activity aims to evaluate the role of education and partnerships between the government, students, and the community in improving the quality of environmental cleanliness through river cleaning activities in Surabaya City organized by the Environmental Agency. Using a Participatory Action Research (PAR) approach focusing on the process of the service and action cycle for sustainable social change, and data was collected through direct observation, documentation, and the active involvement of various stakeholders. The results of the activity indicate that waste management education and community cooperation to improve environmental cleanliness are clearly proven that improvements in environmental conditions and around the river are seen from the decrease in the amount of waste in the river flow, high community participation, and increased quality of public facilities around the activity area. The environmental education carried out in this program also succeeded in deepening the community's understanding of the role of community cooperation and community education in maintaining environmental cleanliness. Furthermore, the activity also fosters sustainable community cooperation as a foundation for creating a healthy and comfortable environment. This community service activity confirms that the integrated role of government, students, and the community is an effective collaboration in addressing waste issues and has the potential to become a collaborative model for other regions in realizing sustainable environmental management. Importantly, this program demonstrates that consistent changes in community behavior can be achieved if supported by ongoing education and strengthening local institutions.